2005
DOI: 10.1158/1078-0432.ccr-05-0267
|View full text |Cite
|
Sign up to set email alerts
|

The Stress-Responsive Gene GADD45G Is a Functional Tumor Suppressor, with Its Response to Environmental Stresses Frequently Disrupted Epigenetically in Multiple Tumors

Abstract: The CpG island of GADD45G was identified as a target sequence during the identification of hypermethylated genes using methylation-sensitive representational difference analysis combined with 5-aza-2V -deoxycytidine demethylation. Located at the commonly deleted region 9q22, GADD45G is a member of the DNA damage-inducible gene family. In response to stress shock, GADD45G inhibits cell growth and induces apoptosis. Same as other GADD45 members, GADD45G is ubiquitously expressed in all normal adult and fetal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
192
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(207 citation statements)
references
References 31 publications
13
192
0
2
Order By: Relevance
“…Normal trachea was chosen as a control since it is readily available and anatomically close to the site of NPC (nasopharynx). In previous experiments Ying et al, 2005;Ying et al, 2006), we confirmed that the gene expression pattern of trachea is similar to that of nasopharynx. Subtracted SSH-PCR products with different sizes were observed in gels between the subtracted and unsubtracted cDNA populations in all three experiments, indicating that the SSH was effective.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Normal trachea was chosen as a control since it is readily available and anatomically close to the site of NPC (nasopharynx). In previous experiments Ying et al, 2005;Ying et al, 2006), we confirmed that the gene expression pattern of trachea is similar to that of nasopharynx. Subtracted SSH-PCR products with different sizes were observed in gels between the subtracted and unsubtracted cDNA populations in all three experiments, indicating that the SSH was effective.…”
Section: Resultssupporting
confidence: 82%
“…Cell lines, tumor and normal tissue samples Cell lines used were: 12 NPC (C666-1, CNE-1, CNE-2, HK1, HNE1, HNE2, HNE3, HONE1, TW-01, BM1, 5-8F and 6-10B) (Glaser et al, 1989;Qiu et al, 2004;Ying et al, 2005), 15 esophageal (EC1, EC18, EC109, HKESC1, HKESC2, SLMT-1, KYSE30, KYSE70, KYSE140, KYSE150, KYSE180, KYSE270, KYSE410, KYSE510 and KYSE520) (Tang et al, 2001;Ying et al, 2006), nine breast (MCF7, ZR-75-1, MB-231; T47D, MB-468, MB-435, SKBR3, BT549, and YCC-B2) (Kim et al, 2005;Ying et al, 2005) and eight cervical carcinoma (HeLa,Caski,C33A,SiHa,808,866,879 and 915) (Steenbergen et al, 2004;Ying et al, 2006). NP69, an SV40 Tantigen-immortalized nasopharyngeal epithelial cell line with many features of normal nasopharyngeal epithelial cells was used as a 'normal' control for NPC (Tsao et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations